2018
DOI: 10.3892/br.2018.1116
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of circulating lncRNA H19 in gastric cancer

Abstract: Gastric cancer (GC) is among the most frequent malignant diseases. Despite advances in treatment, the clinical outcome of patients with GC remains poor. The establishment of novel biomarkers is urgently required for early detection, treatment evaluation and prognostic assessment. Non-coding RNAs (ncRNAs) are a key topic of intensive research due to their potential applications in the field of oncology. The long ncRNA H19 has been frequently reported as overexpressed in many cancers including GC. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…lncRNAs have essential biological functions, and H19 is one of the few well‐characterized lncRNAs, which is an imprinted and maternally expressed transcript . Aberrant expression of H19 has been associated with numerous disease conditions . The current study showed that BA patients had significantly higher levels of H19 mRNA in livers when compared to control subjects, which indicates that H19 may play a role in the pathogenesis of BA.…”
Section: Discussionsupporting
confidence: 51%
“…lncRNAs have essential biological functions, and H19 is one of the few well‐characterized lncRNAs, which is an imprinted and maternally expressed transcript . Aberrant expression of H19 has been associated with numerous disease conditions . The current study showed that BA patients had significantly higher levels of H19 mRNA in livers when compared to control subjects, which indicates that H19 may play a role in the pathogenesis of BA.…”
Section: Discussionsupporting
confidence: 51%
“…H19 is an imprinted and maternally expressed transcript, which is one of the few well-characterized lncRNA [32,33]. Aberrant expression of H19 has been related to a variety of human diseases [34][35][36][37][38]. The current study showed that IPF patients had higher levels of H19 mRNA in lungs when compared to the control subjects using a public datasets, which indicates that H19 may play an important role in the pathogenesis of IPF.…”
Section: Discussionsupporting
confidence: 49%
“…H19-lncRNA regulates gene expression of CDK4, CCND, and certain cancer-related proteins, such as RB1, and indirectly the activity of β-catenin via reduction of CDK8 expression by interacting with macroH2A [68]. H19 lncRNA is highly abundant in many tumors, including CRC [69]. Yoshimizu et al [70] demonstrated that lack of H19-lncRNA expression may be considered as an initiating step in increasing the number of polyp appearance in APC mutated carcinogenesis mice model.…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%